Non-Coding RNAs Regulate Placental Trophoblast Function and Participate in Recurrent Abortion - Chen, Xin; Guo, Duan-Ying; Yin, Tai-Lang; Yang, Jing (Frontiers in Pharmacology, 2021)
Recurrent spontaneous abortion (RSA) is a serious pregnancy complication with an increasing clinical incidence. The various causes of recurrent abortion are complicated. Developments in genetics, immunology, and cell biology have identified important roles of non-coding RNAs (ncRNAs) in the occurrence and progress of recurrent abortion. NcRNAs can affect the growth, migration, and invasion of placental trophoblasts by regulating cell processes such as the cell cycle, apoptosis, and epithelial-mesenchymal transformation. Therefore, their abnormal expression might lead to the occurrence and development of RSA. NcRNAs include small nuclear RNA (snRNA), small nucleolar RNA (snoRNA), ribosomal RNA (rRNA), transfer, RNA (tRNA), circular RNA (cRNA), and Piwi-interacting RNA (piRNA). In this review, we discuss recent research that focused on the function and mechanism of microRNAs (miRNAs), long non-coding RNAs (lncRNAs), and circular RNA (circRNA) in regulating placental trophoblasts. The use of ncRNAs as potential diagnostic and predictive biomarkers in RSA is also discussed to provide future research insights.